Cost Plus Pricing with a Full Costing Approach in Determining the Selling Price of Mie Aigo Bangkalan Bangkalan - Khoirul Anam; Moh. Zidan Rikza; Fadjar Maulana; Mochamad Reza Adiyanto (Indonesian Journal of Economic & Management Sciences, 2023)
This research aims to compare the selling prices applied by the Aigo Bangkalan Noodle Company with the cost plus pricing method using a full costing approach. Apart from that, the aim of this research is also to assess the company's level of efficiency in achieving profits using financial ratios, especially profitability ratios. This research utilizes a descriptive approach, with two types of data used, namely quantitative and qualitative, and adopts interview techniques as a data collection method. Analysis was carried out using descriptive analysis methods. The research findings show a difference in selling prices between companies using a pricing approach based on additional costs (cost plus pricing) and a full costing approach, with a difference of IDR 1,425 (11.42%). However, the Company's performance in generating profits is considered efficient based on evaluation using profitability ratios